Conocimiento financiero y el desempeño laboral del personal del hotel Oro Verde de Iquitos, periodo 2023 - Cardoso Tello, Gladys Luisa (2024)
Financial knowledge is the information that people acquire and that through it, helps them to understand and understand everything related to the management not only of their personal finances, but also, as a business operates with respect to the management of its financial resources; In addition, this knowledge is of great importance since it also allows people to acquire new skills to generate better performance in the performance of their work activities. The investigation is called "Financial knowledge and the work performance of the staff of the Oro Verde Hotel in Iquitos, period 2023", its main objective being to determine how financial knowledge influences the work performance of staff in that period. His study corresponded to a quantitative research and a correlative descriptive design, in which the survey had to be used as a technique and the question questionnaire as a tool to collect data, where it had to be validated by the judgment of three experts and applied to 15 workers. Finally, the results indicate that financial knowledge does not influence the work performance of staff, a situation that is confirmed by the correlation coefficient of Spearman’s Rho that was -0.029.